A SURVEY ON THE READING ATTITUDES OF ENGLISH DEPARTMENT STUDENTS OF FKIP UNIVERSITAS RIAU - Ahmad Safi’i; Fadly Azhar; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Reading is an ability that enables people to acquire information while improving their fluency, vocabulary, and general knowledge. Nonetheless, reading for academic purposes is harder than readers imagine. In the development of reading skills, reading attitude was considered to influence student achievement. This research aims to investigate students' attitudes toward reading English. The research population was the 2018 and 2019 batches of English Department students at FKIP Universitas Riau, with a total sample of 70 students. This research took a quantitative approach, and the research design was a survey design (descriptive analysis). The instrument used to gain the data was an ASRA (Adult Survey of Reading Attitude) questionnaire from Smith (1991), which consisted of 29 items divided into 3 aspects (activity of reading, enjoyment of reading, and anxiety-difficulty). For data analysis, Microsoft Excel and SPSS version 23 were used. The findings revealed that students’ attitudes toward reading were positive, with an average score of 2.60 (SD = 0.83) for reading activity, 2.87 (SD = 0.84) for reading enjoyment, and 2.69 (SD = 0.88) for anxiety-difficulty. The conclusion is that students have a positive attitude toward English reading but still require development in reading activities.Key Words: Attitude, Reading, Reading Attitude, Survey